1987
DOI: 10.1111/j.1525-1594.1987.tb02643.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dialyzer Reprocessing Methods on Complement Activation and Hemodialyzer‐Related Symptoms

Abstract: The effects of different dialyzer processing methods and of reuse on complement activation and dialyzer-related symptoms were studied in 96 maintenance hemodialysis patients. New dialyzers were either unprocessed (Group 1) or machine-washed with bleach and stored in formaldehyde (Group 2). Reused dialyzers were manually cleansed using the combination of bleach and formaldehyde (Group 3), or machine-washed in formaldehyde (Group 4) or peracetic acid (Group 5). Prewashed new dialyzers (Group 2) were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 8 publications
2
17
0
1
Order By: Relevance
“…The significant generation of C3a des Arg on 1st use of CUP and CA was not observed with CUP after reprocessing and was much reduced when CA was reused. In earlier studies, peracetic acid reprocessing was shown to substantially improve leukopenia, complement activation and thrombocyte counts after HD with CUP [30], CA and polysulfone membranes [12]. Our study extends these observations to the newer synthetic mem branes AN69 and PMMA.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The significant generation of C3a des Arg on 1st use of CUP and CA was not observed with CUP after reprocessing and was much reduced when CA was reused. In earlier studies, peracetic acid reprocessing was shown to substantially improve leukopenia, complement activation and thrombocyte counts after HD with CUP [30], CA and polysulfone membranes [12]. Our study extends these observations to the newer synthetic mem branes AN69 and PMMA.…”
Section: Discussionsupporting
confidence: 75%
“…Based on the Kolmogorov-Smirnov [21 ] test, the distribu tions of serum and dialysate P:M concentrations did not deviate sig 30 Westhuyzen/Foreman/Battistutta/Saltissi/ Effects of Reprocessing with Renalin Fleming nificantly from normal (p > 0.118 in all cases). However, the distri bution of plasma C3a concentrations was significantly skewed (p < 0.079 for predialysis, and p < 0.015 all other times).…”
Section: Statistical a Nalysismentioning
confidence: 99%
“…It can be considered to sufficiently wash the dialyzers before using them for each patient, to use a dialyzer sterilized by γ-rays or steam if the reaction was due to the use of a dialyzer sterilized by ethylene oxide, to use a membrane that activates the complement more mildly or to make a transition from those using Angiotensin Converting Enzyme (ACE) inhibitor to those using Angiotensin Receptor Blockers (ARB) (Dumler et al, 1987;Daugirdas & Ing, 1988).…”
Section: Preventionmentioning
confidence: 99%
“…Interestingly, differences in symptoms between new and reused cellulose acetate dia lyzers did not achieved statistical significance, in agree ment with the results from the present study. A subse quent prospective study from the same center again showed that reuse was associated with less symptoms than first use [6]. The dialyzer membranes used in that particular study were saponified cellulose ester and cu prophane; whereas cellulose acetate was used exclusively in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…A number of benefits as well as disadvan tages have been reported to be associated with this pro cedure. Benefits that have been reported include a lower incidence of 'hypersensitivity reactions' [9][10][11], lower intradialytic symptoms [2][3][4][5][6], lower hospitalization rates [3], lower mortality rates [1,7], amelioration of intradia lytic hypoxemia and abnormalities in pulmonary gas transfer [12,13], improvement in biochemical assess ment of biocompatibility such as intradialytic comple ment activation and leukopenia [12][13][14] and financial savings. Disadvantages that have been reported include infection from contaminated dialyzers [16], develop ment of antibody against erythrocytes [17], inadequate dialysis due to loss of membrane surface area, inadvertant employment of another patient's dialyzer, and the unesthetic appearance of reused dialyzers perceived by some patients.…”
Section: Discussionmentioning
confidence: 99%